2015
DOI: 10.1103/physrevd.91.073013
|View full text |Cite
|
Sign up to set email alerts
|

Probing the substructure off0(1370)

Abstract: Within an effective nonlinear chiral Lagrangian framework the substructure of f0 (1370) is studied. The investigation is conducted in the context of a global picture of scalar mesons in which the importance of the underlying connections among scalar mesons below and above 1 GeV is recognized and implemented. These connections are due to the mixings among various quark-antiquarks, fourquarks and glue components and play a central role in understanding the properties of scalar mesons. Iterative Monte Carlo simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 153 publications
2
10
0
Order By: Relevance
“…This later identification of f 0 (1370) is also found in Ref. [50], though with a noticeable four-quark component too. In Ref.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This later identification of f 0 (1370) is also found in Ref. [50], though with a noticeable four-quark component too. In Ref.…”
Section: Resultssupporting
confidence: 80%
“…Similar studies have been carried out in the last years, see for instance [45][46][47][48][49][50][51][52] and references therein.…”
Section: Scalar Couplingssupporting
confidence: 71%
“…Moreover, f 0 (1370) was shown to be predominantly a quark-antiquark state (particularly ss) with small remnant of four quark and glue components. 34 Although there is no experimental data for decay widths of different modes of this broad resonance, Fig. 3 shows that for all the decay modes except ππ, the predicted decay widths are reasonable compared to the full width but Γ[f 0 (1370) → ππ] is extremely large and far from experiment.…”
Section: Figurementioning
confidence: 89%
“…Since this pure four-quark picture is deficient in describing some decay properties of lowest lying scalars and besides the fact that the pure quark-antiquark picture for the next-to-lowest lying scalars can not completely describe their properties, mixing among these states was considered as a solution to this puzzling feature. [27][28][29][30][31][32][33][34][35][36] Mechanism for such mixing in a nonlinear chiral Lagrangian was studied in Ref. 37 and it was shown that due to level repulsion, the lowest lying scalar mesons become lighter and this gives an answer to the question of why scalar mesons are lighter than the axial vector mesons.…”
Section: Introductionmentioning
confidence: 99%
“…At present there is no agreement in literature that among the two strongest candidates, i.e., f 0 (1500) and f 0 (1710), which one is the lightest scalar glueball. While in [23,[57][58][59][60][61], f 0 (1500) is believed to be mostly gluonic, in [62,63] f 0 (1710) was argued to be an unmixed scalar glueball. Moreover the mass obtained from Lattice calculations for the 0 ++ glueball candidate is around 1600 − 1700 MeV with the uncertainty of 100 MeV.…”
Section: Introductionmentioning
confidence: 99%